Maintaining Islamic Values in the Modern World: The Role of Informal Education and Socio-Cultural Dynamics in Rural East Java - Rohmad Rohmad; Roibin Roibin; Ahmad Barizi; Ahmad Walid; Fadhil Akbar (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study examines the internalization of Islamic values in religious-based communities and the factors influencing this process. The objective is to understand how informal education in families and communities shapes children’s Islamic character and to identify related challenges and opportunities. A qualitative approach with a case study method was employed, utilizing participant observation, in-depth interviews with religious figures, parents, and children, and document analysis of community religious activities. Findings suggest that the internalization of Islamic values is most effective through practice-based approaches, such as congregational prayer, reading books, and participating in socio-religious activities. Socio-cultural factors, particularly the culture of collectivism, play a significant role in reinforcing these values, while challenges arise from the influence of digitalization and modernization, which reduce children’s involvement in religious practices. The study emphasizes the need for collaboration among families, communities, and educational institutions to adapt Islamic learning methods to technological changes. It also calls for policies that support community-based informal education to ensure the continued transmission of Islamic values.